DIVERSITY AND ACTIVITY OF GASTROPODS IN MANGROVE TREES IN BAGEK KEMBAR MANGROVE ECOTOURISM AREA, WEST LOMBOK - Mursal Ghazali; Prabowo; Dining Aidil Candri; Tri Wahyu Setyaningrum; Aida Muspiah; Nurhayati (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
The Bagek Kembar Mangrove Ecotourism Area is a rehabilitated mangrove forest area carried out by the government and the community of Cendi Manik Village, Sekotong District. Mangrove forests play a crucial role in human life and the biota associated with them. One of the biota associated with mangrove forests is gastropods. Gastropods are biota that belong to the phylum Mollusca. These biotas can grow and develop well in mangrove forests because mangrove forests provide sufficient food to support the life of these gastropods. This research aims to discover the types and activity of gastropods associated with mangrove forests in the Mangrove Ecotourism Area, Cendi Manik Village, Sekotong District, West Lombok. At the research location, 7 types of gastropod species were associated with mangrove forests. These types of gastropods were P. scutata, T. sulcata, F. javanica, F. ater, T. granifera, S. minata and L. angulifera. All species found are only associated with the Rhizophora and Avicenia Genus. Meanwhile, the gastropod activity found in the Bagek Kembar mangrove forest area serves as a feeding area and shelter.